Addressing five common weaknesses in qualitative research: Sticking feathers together in the hope of producing a duck - Kerr, Philippa (PINS-Psychology in Society, 2022)
This paper identifies a number of common conceptual and methodological weaknesses that crop up in qualitative social science research articles and theses. These weaknesses are: (1) conceptual frameworks with no implications; (2) conceptual frameworks which dominate findings; (3) generic technical jargon in methods sections instead of a transparent account of how the research and analytical decisions actually proceeded; (4) superficial and/or anecdotal results sections; and (5) an overuse of social science jargon that sometimes does not mean very much. Suggestions for improving on these weaknesses are made. It is argued that the validity of a piece of qualitative research is established through coherence among all sections of a paper or thesis – concepts, methods, and findings. The metaphor in the paper’s title conveys the point that simply including the right-sounding terminology or sections in a qualitative research article or thesis in the hope that this will, in and of itself, produce good social science is a strategy about as likely to succeed as sticking feathers together in the hope of eventually producing a duck!